A Sex Difference in the Specificity of Sexual Arousal - Chivers, Meredith L.; Rieger, Gerulf; Latty, Elizabeth; Bailey, J. Michael (Psychological Science, 2004)
Sexual arousal is category-specific in men; heterosexual men are more aroused by female than by male sexual stimuli, whereas homosexual men show the opposite pattern. There is reason to believe that female sexual arousal is organized differently. We assessed genital and subjective sexual arousal to male and female sexual stimuli in women, men, and postoperative male-to-female transsexuals. In contrast to men, women showed little category specificity on either the genital or the subjective measure. Both heterosexual and homosexual women experienced strong genital arousal to both male and female sexual stimuli. Transsexuals showed a category-specific pattern, demonstrating that category specificity can be detected in the neovagina using a photoplethysmographic measure of female genital sexual arousal. In a second study, we showed that our results for females are unlikely to be explained by ascertainment biases. These findings suggest that sexual arousal patterns play fundamentally different roles in male and female sexuality.